# Solve for x: −2(x + 3) = −2(x + 1) − 4

An equation is a mathematical statement with an 'equal to' symbol between two algebraic expressions that have equal values.

## Answer: All real values of x give the solution of the equation −2(x + 3) = −2(x + 1) − 4

An equation is like a weighing balance with equal weights on both sides. If we add or subtract the same number from both sides of an equation, it still holds.

**Explanation:**

−2(x + 3) = −2(x + 1) − 4

- 2x - 6 = -2x - 2 - 4

- 2x - 6 = -2x - 6

Since RHS and LHS are equal for the equation −2(x + 3) = −2(x + 1) − 4